Induction of p53-inducible microRNA miR-34 by gamma radiation and bleomycin are different - Mert, Ufuk; Özgür, Emre; Tiryakioglu, Duygu; Dalay, Nejat; Gezer, Ugur (Frontiers in Genetics, 2012)
microRNAs (miRNAs) are small molecules in their mature form and master regulators of gene expression. Recent work has shown that miRNAs are involved in the p53 network. Of the various miRNAs, miR-34 is regulated by the p53 protein. miR-34 can be induced by ionizing radiation in vitro and in vivo. However, there is no data in the literature for induction of miR-34 by a chemical agent inducing DNA damage. Here we studied the expression of miR-34 in HeLa and MCF-7 cells exposed to genotoxic stress induced by bleomycin or γ-radiation. We first analyzed p53 accumulation upon DNA damage induction. The basal level of p53 in MCF-7 cells was higher (approx. 6fold) than in HeLa cells, and its accumulation was similar for both DNA-damaging agents in both cell lines. We have shown that miR-34 is significantly induced by γ-radiation in HeLa cells, but not in MCF-7 cells. Bleomycin did not significantly affect miR-34 expression in both cell types. In conclusion, our findings reveal that miR-34 induction by genotoxic stress may be cell-type specific.